Subcutaneous adipose tissue alteration in aging process associated with thyroid hormone signaling - Wen-Na Zhang; Hao Zhu; Zhen-Wu Ma; Jing Yu; Yun Yang; Xuan-Bei Lu; Yi-Fan Lv; Xiao-Dong Wang (BMC, 2023)
Abstract Background Functional changes in subcutaneous adipose tissue (SAT) occur earlier in the aging process and play an important role in the occurrence and development of age-related metabolic diseases. The mechanism of this phenomenon is still unclear, and the change in adipose tissue with age is poorly understood. Methods We used transcriptome sequencing (RNA seq) to screen differentially expressed genes at the mRNA level, and analyzed the functional characteristics of the differential genes through GO and KEGG analysis in human SAT of all ages. In order to clarify the specific mechanism of the functional change, we analyzed the chromatin accessibility in the promoter region in the same SAT used in the RNA seq by the assay for transposase-accessible chromatin with high throughput sequencing (ATAC-seq) and obtained the functional genes in SAT changed with age. To verify these changes, we enlarged our sample content of human SAT. The primary mice adipocytes were extracted and stimulated by thyroid hormone of different concentration to construct an animal model, and the expression of the genes were determined through real-time Polymerase Chain Reaction(RT-PCR). The oxygen consumption test and immunofluorescence staining were used to determine the mitochondrial function of SAT. Results RNA-seq showed characteristic gene expression of young and old human SAT, in which 331 genes were up-regulated and 349 genes were down-regulated. ATAC-seq, RNA-seq, combined with the mouse prediction model, determined the functional changed characteristics of seven genes. All these genes expressed differently in SAT of different ages, in which, NCF1, NLRP3, DUOX1 showed positive correlation with age; The expression of IFI30, P2RX1, P2RX6, PRODH, however, decreased with age. And all these genes showed dose dependent alternations under treatment of triiodothyroxine in mice SAT. The oxygen consumption rate revealed significant changes of the mitochondrial function and ROS accumulation in human SAT of different ages. Conclusion In elderly individuals, the function, in addition to distribution, of SAT undergoes significant changes, primarily in mitochondria, which may be due to insensitivity to thyroid hormone signaling. These results identified seven novel genes regulated by thyroid hormone, exhibiting significant changes in SAT of different age, and are probably related to the dysfunction of the aged SAT due to the mitochondrial damage and ROS accumulation.